Major changes and crisis: the impact on women in Latin America and the Caribbean (UN. ECLAC SantiagoCL, 1992)
Examines the crisis, major changes and new uncertainties over a period of approximately 30 years of Latin American and Caribbean development and considers their impact on the female population. Looks at the need to incorporate women into the new ECLAC proposal for changing production patterns with social equity. Addresses new issues facing both women and the societies in which they live. Sums up achievements and obstacles with respect to the status of women in the region and the recommendations made by the member countries at the Fourth Regional Conference.
DC